Mesoporous Titania Gels Prepared from Titanous Chloride and Ammonia: SEM, Nitrogen Adsorption, Thermoporometry and Mercury Porosimetry Studies - Gehane Ghaly; Isabelle Beurroies; Jehane Ragai (Adsorption Science & Technology)
Pore-size distribution studies were carried out employing nitrogen adsorption, mercury porosimetry and thermoporometry techniques on two titania gels prepared from titanous chloride and ammonia using oxygen gas as the oxidizing agent. These gels were also characterized by scanning electron microscopy and X-ray diffraction. After heat-treatment at 340 °C and 520 °C, the gels were found to possess the anatase structure, being predominantly mesoporous in nature as indicated by nitrogen adsorption studies and α S -plots. Very good agreement was observed between the BJH pore-size distribution analysis data and the thermoporometry pore-size determinations. Comparable results were also obtained by mercury porosimetry. The validity of thermoporometry as a viable and reliable technique for pore structure analysis was ascertained.